Ketamine versus alfentanil combined with propofol for sedation in colonoscopy procedures: A randomized prospective study - Türk, Hacer Şebnem; Aydoğmuş, Meltem; Ünsal, Oya; Işıl, Canan Tülay; Citgez, Bülent; Oba, Sibel; Açık, Mehmet Eren (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Different drug combinations are used for sedation in colonoscopy procedures. A ketamine-propofol (ketofol) mixture provides effective sedation and has minimal adverse effects. Alfentanil also provides anesthesia for short surgical procedures by incremental injection as an adjunct. However, no study has investigated the use of ketofol compared with an opioid-propofol combination in colonoscopic procedures. Materials and Methods: A total of 70 patients, ASA physical status I-II, scheduled to undergo elective colonoscopy, were enrolled in this prospective randomized study and allocated to two groups. After premedication, sedation induction was performed with 0.5 mg/kg ketamine +1 mg/kg propofol in Group KP, and 10 mg/kg alfentanil +1 mg/kg propofol in Group AP. Propofol was added when required. Demographic data, colonoscopy duration, recovery time, discharge time, mean arterial pressure (MAP), heart rate (HR), peripheral oxygen saturation, Ramsey Sedation Scale values, colonoscopy patients’ satisfaction scores, and complications were recorded. Results: The need for additional propofol doses was significantly higher in Group AP than in Group KP. MAP at minute 1 and 5, Ramsey Sedation Scale at minute 5, and discharge time were significantly higher in Group KP than in Group AP. Additional propofol doses and total propofol dose were significantly lower in Group KP than in Group AP. Conclusion: Ketofol provided better hemodynamic stability and quality of sedation compared with alfentanil-propofol combination in elective colonoscopy, and required fewer additional propofol; however, it prolonged discharge time. Both combinations can safely be used in colonoscopy sedation.